1970
DOI: 10.1098/rspa.1970.0022
|View full text |Cite
|
Sign up to set email alerts
|

Drop impingement erosion of metals

Abstract: The object of the work has been to investigate experimentally the mechanisms of erosion in metals and alloys under drop impingement attack. For this purpose an apparatus of the wheel and jet type has been used to erode aluminium, copper, iron, cobalt and alloys of these metals. The various stages in the process from the first detectable microplastic deformation to the eventual pitting and removal of material from the surface have been investigated. In addition, experiments were carried out with the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…For water impacting the solid surface at velocities up to v = 1000 m s −1 , the constant k = 2 (Heymann, 1969), and the acoustic velocity, v s , is about 1480 m s −1 (Foldyna et al, 2006). Thomas and Brunton (1970) have shown that the magnitude of the impact pressure is independent of the geometry of the drop but the duration of the pressure is affected by the size and shape of the drop. It lasts for the short period, , that it takes a release wave, generated at the contact edge of the jet, to reach the impact axes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For water impacting the solid surface at velocities up to v = 1000 m s −1 , the constant k = 2 (Heymann, 1969), and the acoustic velocity, v s , is about 1480 m s −1 (Foldyna et al, 2006). Thomas and Brunton (1970) have shown that the magnitude of the impact pressure is independent of the geometry of the drop but the duration of the pressure is affected by the size and shape of the drop. It lasts for the short period, , that it takes a release wave, generated at the contact edge of the jet, to reach the impact axes.…”
Section: Introductionmentioning
confidence: 97%
“…2. When the liquid begins to flow away from the point of impact, there is evidence that the velocity of this tangential flow may be as much as five times the impact velocity (Thomas and Brunton, 1970). Therefore, there are additional shear forces associated with the high-speed flow across the surface acting on the surface in addition to the normal forces.…”
Section: Introductionmentioning
confidence: 97%
“…The failure type of the eroded parts was referred to as a fatigue mechanism due to repeated impacts of the water droplets [8]. Thus, previous studies [9][10][11][12][13] have introduced several mechanical surface treatments as potential solutions to improve the fatigue life of specimens.…”
Section: Introductionmentioning
confidence: 99%
“…When the liquid begins to flow away from the point of impact, there is evidence that the velocity of this tangential flow may be as much as five times the impact velocity (Thomas & Brunton, 1970). The velocity increase is thought to be connected with the shape of the head of the jet.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the impact pressure is independent of the geometry of the drop (Thomas & Brunton, 1970), but the duration of the pressure is affected by the size and shape of the drop. For a sphere or cylinder the corresponding radius or half-width of the contact area R exposed to this pressure is given by…”
Section: Introductionmentioning
confidence: 99%